2018
DOI: 10.1177/1524839918807442
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Infant Friendly Business Designation

Abstract: In response to suboptimal breastfeeding rates, North Dakota added a provision to SB 2344 (public indecency legislation) creating an Infant Friendly business designation for employers providing specified lactation accommodations to employees. However, there has been no evaluation of this designation to determine effectiveness. The purpose of this article is to examine the impact of the Infant Friendly business designation in North Dakota on breastfeeding continuation rates within the context of the social ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 28 publications
0
18
0
11
Order By: Relevance
“…Fourteen studies were included and were reported across eighteen publications, of which nine out of fourteen studies were eligible to be included in the meta-analysis. Two studies (37,38) were ineligible for inclusion in the meta-analysis due to different study designs from other included studies, one study (39) was ineligible due to measuring breast-feeding rate in a different way from other included studies and two studies (40,41) were ineligible as they were qualitative studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies were included and were reported across eighteen publications, of which nine out of fourteen studies were eligible to be included in the meta-analysis. Two studies (37,38) were ineligible for inclusion in the meta-analysis due to different study designs from other included studies, one study (39) was ineligible due to measuring breast-feeding rate in a different way from other included studies and two studies (40,41) were ineligible as they were qualitative studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Four publications were non-randomised controlled studies (38,(42)(43)(44) , and two of these four also included qualitative results from focus groups (43,44) . Nine publications (37,39,(45)(46)(47)(48)(49)(50)(51) reporting eight breast-feeding support programmes were cross-sectional studies, most of which participants had received an intervention. Three publications across two studies reported only qualitative results on women's breast-feeding experiences (40,41,52) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations